Factor of drug rejections and stigma toward drug consumers and drugs / Seema Shamira Muhammad Sani Surinder, Abdul Rauf Ridzuan and Rosilawati Sultan Mohideen - Muhammad Sani Surinder, Seema Shamira; Ridzuan, Abdul Rauf; Sultan Mohideen, Rosilawati (Faculty of Communication & Media Studies, 2019)
This research examined the study of factors of drug rejection and stigma toward drug consumers and drugs. In Malaysia, drug abuse is a complex issue and has been a serious public health problem in Malaysia. The cumulative number of registered drug users until 2008 was estimated at about 250,000 people and was predicted to reach half a million by 2015. By using Raosoft Calculator, the recommended sample size is 271 for this survey. Hence, the researcher manages to get 300 respondents. The first result is based on the Beta value, which shows the most significant relationship between independent towards dependent variables. The results of this study showed and 51.60% of the variance of factor of drug rejections was explained by the stigma of drugs and 27.90% of the variance of factor of drug rejections was explained by the stigma of drug consumers. This study aims to assist AADK and the Home Ministry to provide greater understanding and awareness to the public on the danger of drugs and to have a greater picture of the level of stigma toward drugs and drug consumers in Malaysia. This study is developed to facilitate the Malaysian who have least knowledge and awareness regarding the danger of drug and drug consumers and to provide the Home Ministry, Tan Sri Muhyiddin Yassin and the National Anti-Drugs Agency (AADK) with a superior understanding of the main factor of the Stigma of drug and drug consumers in Malaysia, which will benefit them to plan on how to reduce the number of drug consumers in Malaysia.